The Role of eWOM Credibility, Valence, Brand Attitude, and Perceived Brand Quality through Online Engagement Intention - Hartono; Nur Fitri Rahmawati; Anita Maulina; Diana Prihadini; Supriyono (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines the mechanism linking electronic word-of-mouth (eWOM) and online purchase intention through online engagement intention in the Indonesian digital commerce context. The model integrates the Theory of Planned Behavior, the Elaboration Likelihood Model, and the Brand Equity Theory to explain how informational and evaluative factors shape behavioral outcomes. Data were collected from 304 online consumers with prior experience in reading online reviews and conducting online purchases. Analysis employed Partial Least Squares–Structural Equation Modeling. The results indicate that eWOM credibility has a positive and significant effect on online engagement intention. eWOM valence shows a negative, significant effect, indicating increased consumer skepticism toward directional tone. Brand attitude and perceived brand quality have positive, significant effects on engagement intention. Online engagement intention strongly influences online purchase intention and acts as a full mediating mechanism between all antecedent variables and purchase intention. The model explains 66.6% of the variance in engagement intention and 61.1% of the variance in purchase intention, indicating substantial explanatory power. These findings confirm that engagement represents a critical behavioral activation stage that transforms perception into intention. The study provides empirical evidence that credibility dominates informational influence, while evaluative constructs stabilize consumer behavior under uncertainty. The research addresses a gap in digital environments through a structured mediation mechanism. The findings highlight the importance of trust formation and evaluative consolidation in consumer behavior in emerging digital markets.